A comparative analysis of the financial performance of commercial banks after mergers and acquisitions using Nepalese data - Adhikari Baburam; Marie Kavanagh; Bonnie Hampson (Central Bank Review (CBR), 2023)
This article investigates consolidation and restructuring in the banking sector in Nepal that was induced by regulatory intervention in recent years. We compare the financial performance of the overall commercial banking sector and selected commercial banks on an individual basis before and after the mergers and acquisitions (M&A) policy intervention. The research employs an analysis of the financial ratios (profitability, liquidity, leverage, and wealth of shareholders ratios) before and after mergers that took place between 2013 and 2020 on a sample of seven Nepalese commercial banks. Hypotheses are tested using a paired sample t-test to measure any significant difference between the pre- and post-merger situations of the acquiring banks' financial metrics. The findings indicate that the overall commercial banking sector significantly improved their liquidity and leverage ratios in the post-merger period. Other measures, such as the profitability and shareholder wealth ratios showed either mixed or insignificant results after the M&A. The results for selected commercial banks on an individual basis were even less conclusive and mixed. While some banks showed improvement in financial ratios, other results were insignificant.
Keywords: 330; Mergers and acquisitions; Ratio analysis; Paired t-test; Commercial banks of Nepal; Pre- and post-comparative analysis